Accuracy of diagnostic score by echocardiography for the detection of cardiac amyloidosis in patients with proven extracardiac amyloidosis. (3rd October 2022) - Bauer, F; Fauvel, C H; Raitiere, O; Si Belkacem, N; Colleville, B; Mulder, P
Abstract: Background: In 2021, a position statement of the ESC Working Group on Myocardial and Pericardial Diseases suggested to use an echocardiographic score (i.e., ECHO score) to confirm cardiac amyloidosis (CA) thus to avoid heart biopsy in patients with left ventricular (LV) hypertrophy >12 mm and proven extracardiac amyloidosis. Purpose: To test the accuracy of ECHO-score in a broad spectrum of patients with proven cardiac amyloidosis and anatomical LV hypertrophy measured by echocardiography. Methods: One hundred and twenty patients with proven CA (both from ATTR and AL forms) underwent comprehensive echocardiography including parietal wall thickness (+3 points), Doppler E/e' ratio (+1 point), TAPSE (+2 points), LV global longitudinal strain (1 point) and systolic longitudinal strain apex to base ratio (+3 points) and compared to 13 controls. A score ≥8 points in the presence of LV wall >12 mm which predicts CA, was investigated in patients with LV hypertrophy from 12.1 to 15.0 mm, from 15.1 to 20 mm and over 20 mm. Cardiovascular magnetic resonance (CMR) imaging was available in 63 patients for extracellular volume measurement >0.40% and diffuse late gadolinium enhancement assessment, both present to confirmed amyloidosis. Results: ATTR and AL amyloidosis accounted for 77% and 23%, respectively. Age averaged 76±7yo and 72% of patients were male. LV ejection fraction averaged 61±5%. The ECHO score averaged 6.4±2.5 in patients with LV hypertrophy from 12.1 to 15.0 mm (n=29), 7.9±2.6 in patients with LV hypertrophy from 15.1 to 20.0 mm (n=59) and 9.8±1.7 when LV hypertrophy was >20 mm (n=32). Figure 1 depicts the sensitivity of ECHO score alone and in addition to CMR as a function of LV hypertrophy range. In patients with LV hypertrophy >20 mm, ECHO score alone has a sensitivity near 100% and CMR is useless to confirm cardiac amyloidosis. Between 15.1 to 20.0 mm of hypertrophy, both ECHO and CMR are necessary to reach a sensitivity of 100%. Unfortunately, below 15 mm of LV hypertrophy, neither ECHO nor CMR altogether predict cardiac amyloidosis with good accuracy, meaning heart biopsy is still useful. Conclusion: Upon the degree of LV hypertrophy in a patient with extrcardiac amyloidosis, ECHO score alone or in combination with MRI are efficient only if myocardial parietal thickness is above 15 mm. Funding Acknowledgement: Type of funding sources: None.